The Art of Characterization In Gabriel Sundukyan’s Vaudevilles - Melkonyan, Nora (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The article examines the art of characterization in the vaudevilles of Gabriel Sundukyan and beyond. Gabriel Sundukyan is one of the greatest representatives of Armenian dramaturgy. His vaudevilles constitute an important and irreplaceable part of Armenian theatrical literature. Sundukyan’s vaudevilles are distinguished not only by their comedic structure but also by their deep social subtext and the multilayered development of characters. The author creates typical yet individualized figures that reflect the social relations, moral values, and contradictions of the time. The analysis shows that Sundukyan skillfully combines humor with a critical perspective, revealing social inequality, false morality, and materialism. It is also noteworthy that his characters often bear the influence of cultural intersections, such as the character Yavangul, who represents a fusion of Armenian and Georgian cultures. Through his characters, Sundukyan frequently raises issues related to the moral and social decline of society. His characters often find themselves at the center of internal and external conflicts, facing the clash between old and new values, material interests, and ethical principles. Thus, Sundukyan’s vaudevilles possess not only artistic value but also serve as an important source of socio-philosophical reflection.
Keywords: Philology